Oral clonidine for proctalgia fugax. Issue 8 (August 1987) - Swain, R
Abstract : A report is made of the successful use of oral clonidine for proctalgia fugax by the author on himself. The author, a 30 year old otherwise healthy man, has been having attacks of proctalgia fugax for several years. He had hitherto left the condition untreated. Last year, in a severe attack, he tried oral clonidine 150 micrograms twice a day and found it to be dramatically effective. He was completely relieved in three days and tapered off the drug thereafter. A further attack of proctalgia fugax after a month was again treated successfully with oral clonidine. The presumed aetiology of proctalgia fugax is discussed and the possible mechanism of action of clonidine in this condition is outlined. Further trials of clonidine appear to be worthwhile for this condition which has been described as incurable.